A global review of orange wheat blossom midge, Sitodiplosis mosellana (Géhin) (Diptera: Cecidomyiidae), and integrated pest management strategies for its management. Issue 1 (21st June 2022) - Dufton, S.V.; Olfert, O.O.; Laird, R.A.; Floate, K.D.; Ge, X.; Otani, J.K.
Abstract: Orange wheat blossom midge, Sitodiplosis mosellana (Géhin) (Diptera: Cecidomyiidae), is a major economic pest of wheat ( Triticum aestivum Linnaeus). Here, we review its general biology, history of global spread, economic impact, and methods available to manage its populations. Outbreaks have been reported across the Northern Hemisphere, including in China, Japan, the European Union, the United Kingdom, the United States of America, and Canada. Predators and parasitoids can help attenuate these outbreaks, but control has relied mainly on use of foliar insecticides. Wheat cultivars with resistance to midge conferred by the Sm1 gene became commercially available in 2010 and increasingly are grown to manage midge populations. Forecasting models have been developed in different countries to predict wheat midge populations in an effort to mitigate the degree of economic damage by supporting wheat cultivar selection and to optimise the timing of insecticide applications in conventional wheat production systems. Conservation of natural enemies, insecticides, resistant cultivars, and models combine to form effective integrated pest management programmes for midge, illustrated for Canada with a decision-making flowchart. Future work is needed to address the likely development of midge biotypes with resistance to the Sm1 gene and insecticides currently in use.